2016
DOI: 10.3390/molecules21111589
|View full text |Cite
|
Sign up to set email alerts
|

New Homoisoflavanes, a New Alkaloid and Spirostane Steroids from the Roots of Herreria montevidensis Klotzsch ex Griseb. (Herreriaceae)

Abstract: Abstract:The roots of the South American vine Herreria montevidensis Klotzsch ex Griseb. (Herreriaceae) are used in traditional medicine by several Amerindian groups of the Paraguayan Chaco. Little is known on the chemistry of the plant, despite its widespread use across the South American Chaco. From the ethyl acetate/methanol 1:1 extract of the roots, four new and one known homoisoflavanoid, two flavan derivatives, a stilbene, a new alkaloid, and three new and four known spirostane steroids were isolated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Six novel homoisoflavans, namely, (3 R )-7-methoxy-3-(4-hydroxybenzyl)chroman, (3 R )-7-hydroxy-5-methoxy-6-methyl-3-(4-hydroxybenzyl)chroman, (3 R )-7-hydroxy-5-methoxy-6-methyl-3-(4-hydroxybenzyl)chroman, and (3 R )-7-methoxy-3-(4-hydroxybenzyl)chroman, along with two known homoisoflavans, have been isolated and characterized from the CHCl 3 -soluble fractions by applying HPLC (mobile phase: H 2 O–MeOH 5:5, 3:7). Moreover, two novel homoisoflavans, 7-hydroxy-8-methoxy-3-(4-hydroxybenzyl)-3-chromen and 7-hydroxy-8-methoxy-3-(4-hydroxybenzyl)-3-chromen, could be isolated from the methanolic extract [ 84 ].…”
Section: Chemotaxonomy Of Homoisoflavonoidsmentioning
confidence: 99%
“…Six novel homoisoflavans, namely, (3 R )-7-methoxy-3-(4-hydroxybenzyl)chroman, (3 R )-7-hydroxy-5-methoxy-6-methyl-3-(4-hydroxybenzyl)chroman, (3 R )-7-hydroxy-5-methoxy-6-methyl-3-(4-hydroxybenzyl)chroman, and (3 R )-7-methoxy-3-(4-hydroxybenzyl)chroman, along with two known homoisoflavans, have been isolated and characterized from the CHCl 3 -soluble fractions by applying HPLC (mobile phase: H 2 O–MeOH 5:5, 3:7). Moreover, two novel homoisoflavans, 7-hydroxy-8-methoxy-3-(4-hydroxybenzyl)-3-chromen and 7-hydroxy-8-methoxy-3-(4-hydroxybenzyl)-3-chromen, could be isolated from the methanolic extract [ 84 ].…”
Section: Chemotaxonomy Of Homoisoflavonoidsmentioning
confidence: 99%
“…36 Zhao et al 37 reported the isolation of the 3-benzylchromen 20 (Figure 4) from C. sappan and observed that this may have been the first natural product possessing a double bond located at C-3 and C-4 of a homoisoflavan system. In 2016 came a further report on the isolation of 3 more similar Δ 3,4 -unsaturated compounds, but with additional hydroxy and methoxy substituents 38,39 from Caesalpina spinosa and Herreria montevidensis, respectively. Interestingly, He et al also reported 2 more compounds 23 and 24 from the same plant, which contain a carbonyl group at C-2.…”
Section: Novel Structures Containing the Hif Skeletonmentioning
confidence: 99%
“…A total of 15 homoisoflavanes has been reported to date since the discovery of ( S )-3-(4-hydroxybenzyl)­chroman-7-ol (Figure ). The new homoisoflavane dracaeconolide B, 3-(4-hydroxybenzyl)-7-hydroxy-5,8-dimethoxychromane, has been recently isolated from the red resin of Dracaena cochinchinensis (Lour.) S.C. Chen (Liliaceae) .…”
mentioning
confidence: 99%